Sapu Malaysia - Faisal Mustaffa (Petaling Jaya, Selangor : Orange Dove, 2010)
Politics and government in Malaysia; caricatures and cartoons.
In Malay.
Keywords: Comic books, strip, -- Social aspect -- Malaysia; Malaysian wit and humor, Pictorial; Malaysia -- Politics and government -- Caricatures and cartoons